2021
DOI: 10.3390/children8080705
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Affordances for Motor Behavior of Schoolchildren (AMBS) and Motor Competence Assessment (MCA) in Brazilian Children

Abstract: During growth, children are influenced by an extensive network, in which more favorable contexts provide better affordance landscapes, and consequently have a better potential to foster child development. We aimed to examine the affordances provided to children using the Affordances for Motor Behavior of Schoolchildren (AMBS) tool, estimating its association with children’s motor competence, as assessed by the Motor Competence Assessment (MCA) battery. Seventy-two Brazilian children were evaluated using the MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, other factors beyond obesity, such as socioeconomic status [20,21], culture and/or geographical location [22], mother education [23,24], resources of the domestic environment [25], resources of the school [26] and PA levels [27][28][29][30], may influence gross MC. Thus it is crucial to match groups concerning these factors to avoid interpretation bias.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other factors beyond obesity, such as socioeconomic status [20,21], culture and/or geographical location [22], mother education [23,24], resources of the domestic environment [25], resources of the school [26] and PA levels [27][28][29][30], may influence gross MC. Thus it is crucial to match groups concerning these factors to avoid interpretation bias.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the affordances for motor development in the home environment, parents of young children with and without CHARGE syndrome completed a validated survey on affordances in the home environment, AHEMD [7,25]. The rationale for this research is that more affordances in the home afford children more opportunities for movement experiences and physical activity that can promote fine and gross motor development [26]. This notion is based upon the ecological theory in which environments have individuals, objects, places, and events that provide action opportunities [6].…”
Section: Discussionmentioning
confidence: 99%
“…Some past investigations showed that MC is associated with the development of healthy lifestyles [12,13,30], can be a significant predictor of metabolic syndrome in children and adolescents [31], is associated with flexibility in adolescents [32], is reliable to assess youth volleyball players MC [33], and can influence the perceived exertion in young adults [34]. Researchers also compared MC regarding their country [35,36], sex [37,38], and the quality of their environments and affordances provided [39]. Different reviews are showing that MC is a complex biocultural construct and, its investigation requires a transdisciplinary approach [40,41].…”
Section: Plos Onementioning
confidence: 99%